Projeto de um nebulizador autopropelido para aplicação de inseticidas no combate aos mosquitos: fases informacional e conceitual - Baumhardt, Ulisses Benedetti (2009)
There are many diseases transmitted by mosquitoes and, among them, dengue has been standing out in the last years by the increasing and elevated numbers of infected people, being considered as one of the principal problems of the public health in the world. In view of the use of agricultural techniques for the control of the vector, as the application of pesticides through the chemical treatment of the environment and the absence of a specific equipment for the control in high scale, the aim of this work was the development of a concept of a machine for such purpose, which attends satisfactorily to the requirements of the clients/users, making it possible to maximize the efficiency obtained nowadays in this process. Among the characteristics present in the concept, are: the presence of two mouth aerosol generators instantaneously adjustable by the operator from his cabin of work; the possibility of simultaneous aerosol generation for both sides perpendicular to the direction of the moving of the machine and the presence of individual cabins for the driver and the operator of the aerosol generator.